Integrated multifactor assessment of road geometry, vehicle types and weather diversity on bilateral transverse slopes: Bridging gaps in dynamic modeling - Mahdi Moharami; Ali Abdi Kordani; Akram Kohansal; Farzad Moradi (PLoS ONE, 2026)
Lane-changing maneuvers are critical to road safety and are significantly influenced by road geometry, particularly transverse slopes. This study investigates how bilateral transverse slopes affect vehicle dynamics during lane changes and their implications for safety. Using advanced simulation tools, CarSim and TruckSim, a comprehensive model was developed incorporating vehicle types, speeds, weather conditions, and driver behaviors. The analysis covered three vehicle categories—sedans, SUVs, and trucks—across four transverse slope variations (0%, 1.5%, 2%, and 2.5%) under three weather conditions: dry, rainy, and snowy. Key dynamic parameters such as steering angle, slip angle, rollover angle, and torsional moment angle were examined to evaluate each vehicle’s stability and behavior throughout lane-changing maneuvers. The results show that increasing transverse slopes moderately affect steering and rollover angles, while slip angles and torsional moments remain largely stable for all vehicle types. Trucks demonstrated the highest sensitivity to speed and slope changes, with control challenges arising at speeds above 90 km/h on higher slopes. In contrast, sedans and SUVs exhibited stable behavior with minimal variations in the safety parameters measured. Additionally, adverse weather conditions—especially snowy roads characterized by low friction coefficients (0.28)—amplify instability risks across all vehicles. In conclusion, bilateral transverse slopes, primarily implemented for drainage purposes, can be safely incorporated into suburban road designs with slopes up to 2.5% without significantly compromising vehicle stability. These findings offer important insights for optimizing road geometry, enhancing vehicle safety systems like Electronic Stability Control (ESC), and reducing rollover risks under a variety of driving conditions.